A study on factors that influence non-muslim customers to patronise products of islamic banking in Kota Kinabalu / Mohd. Japar Salijan - Salijan, Mohd Japar (2015)
The introduction of Islamic banking system in the last years of twenty century have created a new way of applying banking affairs on the basis of Islamic principles. Scholars believe that the scheme is stable in its nature and would enhance the economic development of countries that applied the system. Due to high competition in banking industry of Malaysia, Islamic banks are competitively innovating new products in order to have higher market share and remain competitive. There are several financial products and services that have been offered by the Islamic Banks. This Islamic products and services need to be marketed to better position Islamic Banks with diversity portfolio of products and services. Therefore, this conceptual paper intends to provide a framework that influence different groups of bank customers in the adoption and usage intention of Islamic Banks' products and services. The findings revealed that Islamic Banks' reputation and status, services and facilities (performance), profitability, Syaria'ah Compliance (religious perspective) and customers' perception (for example trust and attitude)have significant relationship in the area of adoption studies has been justified as major determinants in regards with the adoption of Islamic Banks' products and services in context of Kota Kinabalu, current study extends useful determinants for non-Muslim to adopt the Islamic Banks' products and services in Sabah. The findings of the study would be useful for decision makers in expanding a better future for Islamic banking and financial instruments.